Sensor Platform with a Custom‐tailored Aptamer for Diagnosis of Synthetic Cannabinoids. Issue 3 (7th January 2020) - Balaban, Simge; Man, Ezgi; Durmus, Ceren; Bor, Gulsah; Ceylan, Ayse Elcin; Pinar Gumus, Z.; Evran, Serap; Coskunol, Hakan; Timur, Suna
Abstract: Synthetic cannabinoids (SCs) are the large group of abused drugs and detection of them is still a challenge. Hence, new methods for analysis of SCs are being investigated. We aimed to develop a novel system for selective analysis of SCs. First, various custom‐tailored aptamers against the target SCs were selected through GO‐SELEX process. Toggling between different SC analytes during successive rounds of selection was performed to generate cross‐reactive aptamers. Then, the amino‐capped aptamers were synthesized and easily attached to the cysteamine‐covered gold electrodes. Analytical parameters and selectivity of the aptasensors were compared by using electrochemical techniques. After comparison of the analytical features and selectivity towards target analytes, one of the aptamers designated as Apta‐1 was chosen for further measurements. The aptasensor was tested by using differential pulse voltammetry technique against JWH‐018 (5‐pentanoic acid), selected as a model for SCs. The linearity and limit of detection were determined as 0.01–1.0 ng/mL and 0.036 ng/mL. Finally, sample application in synthetic urine samples was successfully performed with standard addition method, as confirmed by LC‐QTOF/MS. JWH‐018 (4‐hydroxypentyl), JWH‐073 (3‐hydroxybutyl), JWH‐250 (5‐hidroxypentyl) and HU‐210 were used to test the selectivity of the aptasensor and the system was shown to recognize all these SCs. Also other illegal drugs did not significantly interfere with the signal responses. Abstract :